THE PROBLEM OF ABLEISM AS A NEGATIVE WORLDVIEW OF SOCIETY - Nosyreva, Alyona Evgenievna (International Journal of Law in Changing World, 2024)
In essence, ableism as a sociocultural phenomenon reflects society’s individual and social attitudes, which leads to the devaluation of the legal status of individuals and restrictions in the implementation of their constitutional rights and freedoms, which determines the socio-legal significance of the chosen topic. This work aims to present a comprehensive analysis of the ontology of human rights from the point of view of international standards and foreign sources. To achieve this objective, the author attempted to determine the historical origin of ableism as a social phenomenon, its legal nature and its main types, and to point out scientific assumptions to combat discrimination. The research employed the following methods: logical, formal-legal, and system analysis. Based on the results, the author identified current theoretical and empirical problems of ableism and developed his understanding of the legal protection of the rights and fundamental freedoms of people with disabilities. This work presents a systemic and comprehensive examination of what societies consider discrimination against people with disabilities and its legal consequences. It expands the understanding and significance of ensuring constitutional guarantees for citizens and draws attention to the social difficulties of people with disabilities. __________ En esencia, el capacitismo como fenómeno sociocultural refleja las actitudes individuales y sociales de la sociedad, lo que conduce a la devaluación del estatus legal de los individuos y a restricciones en la implementación de sus derechos y libertades constitucionales, lo que determina la relevancia sociojurídica del tema elegido. Este trabajo tiene como objetivo presentar un análisis integral de la ontología de los derechos humanos desde el punto de vista de los estándares internacionales y fuentes extranjeras. Para lograr este objetivo, el autor intentó determinar el origen histórico del capacitismo como fenómeno social, su naturaleza jurídica y sus principales tipos, además de señalar supuestos científicos para combatir la discriminación. La investigación empleó los siguientes métodos: lógico, jurídico-formal y análisis sistémico. Con base en los resultados, el autor identificó problemas teóricos y empíricos actuales del capacitismo y desarrolló su comprensión sobre la protección legal de los derechos y libertades fundamentales de las personas con discapacidad. Este trabajo presenta un examen sistemático y completo de lo que las sociedades consideran discriminación contra las personas con discapacidad y sus consecuencias legales. Amplía la comprensión y la importancia de garantizar las garantías constitucionales para los ciudadanos y llama la atención sobre las dificultades sociales de las personas con discapacidad. __________ 本质上，能力歧视作为一种社会文化现象，反映了社会的个体和社会态度，导致了对个人法律地位的贬低以及其宪法权利和自由在实施中的限制，从而确定了所选主题的社会法律重要性。本研究旨在从国际标准和外国资料的角度，全面分析人权的本体论。为实现这一目标，作者试图确定能力歧视作为一种社会现象的历史起源，其法律本质及其主要类型，并指出了应对歧视的科学假设。本研究采用了以下方法：逻辑分析、形式法律分析和系统分析。基于研究结果，作者识别了能力歧视的当前理论和实践问题，并发展了对保护残疾人权利与基本自由的法律理解。本研究系统且全面地审视了社会对残疾人歧视的定义及其法律后果。它拓展了对确保公民宪法保障的重要性和意义的认识，并引起了对残疾人社会困境的关注。